Militia Portalis - Sebők, Ferenc (Tools of war, 2023)
The militia portalis system was introduced in Hungary in 1397. According to royal decree, each landowner was required to equip one mounted archer for every 20 peasant plots (porta) on his estate. Members of the lesser nobility were required to join their financial resources and do the same for every 20 peasant plots. This system was employed against the Ottomans and other opponents of the realm, though it was most effective against Turkish light cavalry, as their way of warfare was similar to that of Hungarian light cavalry. Warriors serving in the banderia of ecclesiastical and secular lords cannot be regarded as mercenaries in the proper sense of the word (though sometimes they received money for their services) – in most cases they served their lords for subsistence, provisions, land donations, and support for rise in social status. From a military point of view, the soldiers of ecclesiastical banderia were the most effective, and the ones serving in the units of secular lords and the counties were less useful on the battlefield. During the rule of King Matthias (1458–1490) the first mercenary army in Hungarian history was organised, but the militia portalis system was also upheld. In the Jagiellonian period (1490–1526) the system was reinvigorated and served successfully against smaller-scale Ottoman forces, but it was incapable of withstanding the all-out attacks in 1521 and 1526.